Spectral characteristics of spring arctic mesosphere dynamics - Hall, C. M.; Manson, A. H.; Meek, C. E. (HAL CCSD, 1998)
International audience The spring of 1997 has represented a stable period of operation for the joint University of Tromsø / University of Saskatchewan MF radar, being between refurbishment and upgrades. We examine the horizontal winds from the February to June inclusive and also include estimates of energy dissipation rates derived from signal fading times and presented as upper limits on the turbulent energy dissipation rate, ? . Here we address the periodicity in the dynamics of the upper mesosphere for time scales from hours to one month. Thus, we are able to examine the changes in the spectral signature of the mesospheric dynamics during the transition from winter to summer states.